Code mixing in Pesantren Students' Conversation: Case Study in SMP and PesantrenBumi Cendekia - Atibrata, Tyas Gita (Universitas Negeri Yogyakarta, 2024)
This study aims to determine the reasons and types of code mixing English and Indonesian used by seventh grade students' conversations in SMP and Pesantren Bumi Cendekia. This research is a qualitative descriptive research. The instruments of this research are: recording and direct observation of student conversations as well as in-depth interviews with related parties. analysis of the data using the theory of analysis of Miles and Huberman. The research subjects consisted of all seventh grade students of SMP and Pesantren Bumi Cendekia, when they doing activities in class and in the canteen. The results of research found that First, Types of code mixing found from 79 data is 72 utterances of insertion, 15 utterances of alternation, and 7 utterances of congruent lexicalization. Secondly, there are 9 reasons students used code mixing at SMP Bumi Cendekia. Broadly the reason of students used code mixing because of the limited vocabularies and to minimize misunderstandings in communication.